A historiografia da mineiridade: trajetórias e significados na história republicana do Brasil - Walderez Simoes Costa Ramalho (2015)
This dissertation approaches the narratives of historical interpretation about Minas Gerais produced during the twentieth century, which are referred here as historiography of mineiridade. The purpose is to investigate how these texts articulated meanings to the experience of time in Minas in order to perceive how the versions of an alleged regional identity were built. The path chosen by this study begins with a theoretical discussion about the relations among history, historiography and identity construction. Once established the theoretical references, a two-hand analysis is performed. First, the texts are situated according to their respective contexts. This enables not only to understand the similarities and differences among the characterizations, as well as the transitions between the essentialist formulation (the identity as something fixed to be discovered by the observer) and the non-essentialist one (the identity as an unfinished process and built according to interests, positions and expectations), which marked the historiography of mineiridade. Second, one seeks an organization of the main themes and meanings presented in the referred texts in order to understand the structure of the speech in an overview. Thus, it was possible to discern the most important content in the sources and the predominantly conservative content in them. Such exercise of critical historiography should help in the search for critical positions to the essentialist-traditional discourse of mineiridade.